The Fourier analysis of picosecond acoustic signals generated by laser beam in Au/V nanolayers - Aleksiejuk, M.; Rejmund, Feliks (Archives of Acoustics, 2006)
Paper presents the results of study of picosecond acoustic signals generated by femtosecondlaser pump pulse in Au/V multilayers. Au/V nanostructures with a period of 36-205Ålocated on MgO substrate were studied. The dependence of measured changes of the laserlight reflectivity from nanostructure surface on different delays of probe beam was examined.Peak frequencies obtained by FFT analysis were interpreted as frequencies of acoustical localizedmodes. The obtained values of these localized modes are in agreement with numericalresults. In the same sample localized modes were excited simultaneously in the first and secondfrequency forbidden gaps.